Data supporting the publication "Programmable synthetic magnetism and chiral edge states in nano-optomechanical quantum Hall networks" - Slim, Jesse J.; del Pino, Javier; Verhagen, Ewold (My University, 2025)
Data supporting the publication "Programmable synthetic magnetism and chiral edge states in nano-optomechanical quantum Hall networks"
Keywords: 530